The Effect of Parental Rejection on Children’s Personality Depicted in The Willoughbys (2020) - Dian Ari Safitri; Mia Fitria Agustina; Ririn Kurnia Trisnawati (Buletin Al-Turas, 2023)
PurposeThis current study aimed to analyze the effect of parental rejection on children in The Willoughbys (2020) movie. The focus of discussion in this study was centered on the first child of the Willoughbys family, namely Tim Willoughby.  MethodThe method used to help analyze the data is a qualitative method. The data are taken from pictures and dialogues from the movies. Through the psychological approach, this study implemented Parental-Rejection Theory (PARTheory) to help analyze the effect of parental rejection presented in the movie.  Results/findingsThe study showed that parental rejection affects children socially and emotionally.  It influenced some aspects of children’s life. Tim Willoughby suggested that parental rejection affected his perspective of the world, his dependency level, his relationship with others, and also his mental state.  ConclusionThe study concluded that the consequences of parental rejection contain features that can have the potential to last for a long time. Therefore, this study suggests that parents must take into consideration of their words as well as actions toward their children. They also have to pay close attention to their children’s development so that they can intervene if children show any symptoms that indicate problems.